Dynamic Response of Cement–Fly Ash Mixed Pile Composite Foundation Under Wave Load - Zhang, Haojin; Zhou, Shengquan; Wang, Rui; Li, Dongwei (Frontiers in Earth Science, 2022)
CFMPs (cement and fly ash mixing piles) are used to reinforce fly ash foundation to solve the problem of a large amount of fly ash accumulation in coastal areas. CFMP-fly ash composite foundation is used as the foundation of coastal and coastal engineering. Through the indoor model test, the bearing characteristics and load transfer mechanism of CFMP-fly ash composite foundation under wave load were investigated. The results show that with the increase of wave load, the horizontal resistance of the fly ash stratum increases gradually, the soil resistance moves down, and the level of resistance shows nonlinear characteristics. The pile bending moment, pile displacement, and horizontal resistance of the CFMP composite foundation are concentrated in the upper pile and fly ash stratum, which can improve the ability of the composite foundation to resist horizontal load by improving the physical and mechanical properties of the upper fly ash stratum. Through the calculation of the load–displacement curve, it is found that the measured displacement value is closer to that obtained using the p–y curve method (a method for solving nonlinear lateral resistance of piles). The hysteretic curve area of cyclic loading decreases with the increase of cyclic number. The accumulation of elastoplastic deformation of pile shows that the properties of fly ash gradually change to elastic stage, cyclic loading can reduce the horizontal deformation modulus of composite foundation CFMP caused pile—fly ash system of weakening, in peak load reaches level under the critical state displacement curve showed a trend of the rapid growth of nonlinear, cyclic cumulative failure occurs, and the cyclic load limit state is reached, which affects the service performance of the whole structure.